Ease: Ezetimibe Add-on to Statin for Effectiveness Trail - Brokes, Linda (Nepalese Heart Journal, 2006)
Results from the largest community-based clinical trial to date, involving more than 3000 patients, has shown that adding the cholesterol absorption inhibitor ezetimibe to ongoing stable statin therapy in patients with hypercholesterolemia produces a significant additional reduction in low-density lipoprotein (LDL)- cholesterol compared with adding a placebo.[1] In addition, more patients who added ezetimibe achieved their National Cholesterol Education Program Adult Treatment Panel (NCEP ATP) If LDL-cholesterol targets. The Ezetimibe Add-on to Statin for Effectiveness (EASE) trial included a total of 3030 patients on a stable dose of a statin but not yet at their NCEP ATP III LDLcholesterel goal,[2]